Prevalence of radiographic lumbar spondylosis and its association with low back pain in elderly subjects of population-based cohorts: the ROAD study. Issue 9 (21st August 2008) - Muraki, S; Oka, H; Akune, T; Mabuchi, A; En-yo, Y; Yoshida, M; Saika, A; Suzuki, T; Yoshida, H; Ishibashi, H; Yamamoto, S; Nakamura, K; et al.
Abstract : Objectives: Although lumbar spondylosis is a major cause of low back pain and disability in elderly people, few epidemiological studies have been performed. The prevalence of radiographic lumbar spondylosis was investigated in a large-scale population study and the association with low back pain was examined. Methods: From a nationwide cohort study (Research on Osteoarthritis Against Disability; ROAD), 2288 participants aged ⩾60 years (818 men and 1470 women) living in urban, mountainous and coastal communities were analysed. The radiographic severity at lumbar intervertebral levels from L1/2 to L5/S was determined by Kellgren/Lawrence (KL) grading. Results: In the overall population the prevalence of radiographic spondylosis with KL⩾2 and ⩾3 at the severest intervertebral level was 75.8% and 50.4%, respectively, and that of low back pain was 28.8%. Although KL⩾2 spondylosis was more prevalent in men, KL⩾3 spondylosis and low back pain were more prevalent in women. Age and body mass index were risk factors for both KL ⩾2 and KL⩾3 spondylosis. Although KL = 2 spondylosis was not significantly associated with low back pain compared with KL = 0 or 1, KL⩾3 spondylosis was related to the pain only in women. Conclusions: This cross-sectional study in a large population revealed a high prevalence of radiographic lumbar spondylosis in elderly subjects. Gender seems to be distinctly associated with KL⩾2 and KL⩾3 lumbar spondylosis, and disc space narrowing with or without osteophytosis in women may be a risk factor for low back pain.